LEP G2548A polymorphism is associated with increased serum leptin and insulin resistance among T2DM Malaysian patients - Ahmed Ali, Layth; Jemon, Khairunadwa; Ab Latif, Nurriza; Abu Bakar, Suhaili; Syed Alwi, Sharifah Sakinah (China Medical University, 2021)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic syndrome that is rapidly increasing across the world, especially in Malaysia. Leptin plays a vital role in the regulation of metabolism through its effect on peripheral tissues. G2548A polymorphism in the LEP gene promoter has been associated with insulin resistance, leptin, and type 2 diabetes mellitus across different population, but has not been inclusively reported within the Malaysian population. Objective: Thus, our study aimed to investigate the impact of G2548A polymorphism on serum leptin levels and insulin resistance among Malaysian T2DM patients. Methods: This case-control study involved 150 T2DM patients and 150 non-diabetic volunteers from ethnic Malays, Chinese and Indians. Genotyping of G2548A polymorphism was carried out using PCR-RFLP. Serum leptin and insulin levels were determined via ELISA. ANOVA and Chi-square tests were used to determine the distribution of genotypes and allelic frequencies based on serum leptin and insulin levels. Results: Frequency of AA genotype and A allele of G2548A variant were significantly (P < 0.05) higher in T2DM patients of Malay and Indian ethnicities (4%, 35%, and 36%, 57%, respectively) as compared to the control groups (0%, 22%, and 18%, 35%, respectively). Fasting serum leptin levels were significantly (P < 0.001) higher in T2DM patients compared to non-diabetic subjects (166.78 pg/ml, 101.94 pg/ml, respectively). Additionally, elevated serum leptin, insulin levels, and BMI in diabetic patients were found to be associated with the AA genotype of this variant, compared to GG, and GA genotypes (P < 0.05). Conclusion: Our findings suggest a significant association between G2548A polymorphism among Malaysian T2DM subjects, particularly among Malay and Indian ethnic groups. Moreover, the A allele frequency of the G2548A variant significantly increased the risk of T2DM and is significantly associated with increased serum leptin, insulin levels, and elevated BMI.